Divergent Reactivity of δ- and β'-Acetoxy Allenoates with 2-Sulfonamidoindoles via Phosphine Catalysis: Entry to Dihydro-α-carboline, α-Carboline, and Spiro-cyclopentene Motifs - Debnath, Shubham; Kumar, A. Sanjeeva; Chauhan, Sachin; Swamy, K. C. Kumara (Journal of organic chemistry, 2021)
The reactivity of 2-sulfonamidoindoles with acetoxy allenoates under phosphine catalysis depends on the disposition of the acetoxy (OAc) group on the allenoate. In the temperature-controlled [3 + 3] annulations, d-acetoxy allenoates afforded dihydrocarboline and carboline scaffolds with carbon-nitrogen nucleophilic 2-sulfonamidoindoles, in which allenoate serves as a beta-, gamma-, and delta-carbon donor. At room temperature (25 degrees C), dihydro-alpha-carboline motifs were obtained exclusively through Michael addition, 1,4-proton shift, isomerization, 1,2-proton transfer, phosphine elimination, and aza-Michael addition. The higher temperature (80 degrees C) cascade protocol using Ph3P-Cs2CO3 combination involves addition-elimination, aza-Claisen rearrangement, tosyl migration, and aromatization as key steps to give alpha-carbolines containing tosyl functionality at the gamma-carbon. In contrast, with beta'-acetoxy allenoate, 2-sulfonamidoindole acts only as a carbo-nucleophile in (p-tolyl)(3)P-directed [4 + 1] spiro-annulation, leading to five-membered spiro-carbocyclic motifs essentially as single diastereomers (dr >20:1) via chemoselective carbo-annulation.